Renal survival and its prognostic factors in chronic kidney disease patients in Hospital Universiti Sains Malaysia, Kelantan - Omar, Fatin Farhanah Haji (2016)
Introduction: End Stage of Renal Disease (ESRD) in Chronic Kidney Disease (CKD) patients represents a heavy burden for patients, families, and health care systems. Objectives: The objectives of this study were to determine the renal survival time of CKD patients at Hospital USM and to identify the prognostic factors that influence the renal survival of patients. Methodology: A retrospective cohort study was conducted involving 247 CKD patients at Hospital USM, Kelantan from January 2005 until December 2015. All patients who fulfilled the criteria were included in the study. The medical record were reviewed and the renal survival time based on the time of the first date of diagnosis with CKD until the the first date of diagnosis with ESRD or received dialysis. The Kaplan-Meier and Cox proportional hazard regression analyses were used in the statistical analysis. Results: Overall renal survival time of CKD patients was 26 months. The significant prognostic factors that influence the renal survival of CKD patients were GFR (adjusted hazard ratio (HR)=0.96, 95% confidence interval (CI): 0.98,0.99; p value <0.001), smoking status (adjusted HR=2.19, 95% CI: 1.53, 3.13; p value=0.042), comorbid hyperlipidemia (adjusted HR=1.87, 95% CI: 1.34,2.60; p value =0.005), analgesics (adjusted HR=1.87, 95% CI: 1.21,2.88; p value =0.015), functional GI disorder (adjusted HR=1.42, 95% CI:1.07,2.01; p value =0.016), lipid lowering agents (adjusted HR=1.41, 95% CI: 1.02,1.97; p value=0.039), corticosteroid (adjusted HR=2.10, 95% CI: 1.25,3.55; p value =0.005), urea (adjusted HR=1.03, 95% CI: 1.01,1.05; p value <0.001), and creatinine (adjusted HR=0.99, 95% CI: 0.98,1.00; p value =0.005). Conclusion: The medium renal survival time of CKD patients in this study very fast within 26 month. The prognostic factors of renal survival identified were GFR level, smoking status, comorbid hyperlipidemia, analgesics, lipid lowering agents, functional GI disorder, corticosteroid drugs, urea and creatinine are significant to renal survival among CKD patients in Hospital USM. Thus, the clinician can change the clinical management by focus on the factors and slow the progression to ESRD.